Porcine reproductive and respiratory syndrome virus (PRRSV) in pig meat - Raymond, Philippe (Can J Vet Res, 2017)
Porcine reproductive and respiratory syndrome, caused by the porcine reproductive and respiratory syndrome virus (PRRSV), is an economically important disease in the swine industry. Previous studies demonstrated the presence of the virus in pig meat and its transmissibility by oral consumption. This study further analyzed the infectivity of PRRSV in commercial pig meat. Fresh bottom meat pieces (n = 1500) randomly selected over a period of 2 y from a pork ham boning plant located in Quebec, Canada, were tested by reverse transcriptase polymerase chain reaction (RT-PCR). Each trimmed meat was stored in the plant freezer, subsampled weekly for up to 15 wk, and tested with quantitative RT-PCR to determine the viral load. Meat infectivity was evaluated using specific pathogen-free piglets, each fed with approximately 500 g of meat at the end of the storage time. Genotype-specific RT-PCR confirmed the presence of PRRSV mainly during cold weather in 0.73% of the fresh meat pieces. Wild and vaccine strains of genotype 2 were detected. Porcine reproductive and respiratory syndrome virus nucleic acid was stable in meat stored at around −20°C during the 15 wk. Serological and molecular analysis showed the transmission of infection by a majority of PRRSV positive meat pieces (5/9) fed orally to naïve recipients. The results confirmed a low prevalence of PRRSV in market’s pig meat, and virus transmissibility by oral consumption to naïve recipients even after several weeks of storage in a commercial freezer. It occurred mainly with meat harboring the highest PRRSV RNA copies, in the range of 10(9) copies per 500 g of meat, with both wild type and vaccine-related strains.